Importance of financial and insurance markets integration for CGCED countries : discussion draft - Auffret, Philippe ([s.n.[ [S.l.], 2000)
Outlines important characteristics of countries which belong to the Caribbean Group for Cooperation in Economic Development (CGCED). Examines the relationship between the economic costs generated by variations in consumption to: country size; the depths of financial and insurance markets; and overall level of economic development. Shows that these costs could be substantially reduced in CGCED countries by integrating their capital markets within the region and the rest of the world. Presents policy recommendations. Concludes by outlining ways in which the World Bank could help foster domestic depths and international integration of both financial and insurance markets.\n